Analisis Pengaruh Trust In Brand Terhadap Brand Loyalty Pada Notebook Merek Lenovo di Kota Mataram - Muhamad Sayuti (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
This research was done to the citizen of Mataram City Province of West Nusa Tenggara and aim to analyze the influencing of brand loyalty that is brand charateristic, company characteristic and brand-consumer characteristic. This research hypothesis was anticipated by a independent variable influencing by significant have an positive effect on to brand loyalty and anticipated by a brand-consumer characteristic variable have an effect on more dominant than another variable. This research use the appliance of data taken (instrument) in the form of questionaire laying open about brand charateristic, company characteristic and brand-consumer characteristic. So that data taken by good hence questionaire have to be up to standard of validity and reliability. Analysis technique used at this research was multiple linier regression analysis to know the accurate independent variable influencing either through simultaneously and also partially to dependent variable. As for multiple linier regression model have to be up to standard of common/public assumption of regression by doing/conducting test normallity, multicolinearity, and heteroscedastisity. Pursuant to result analyze the F test proven by that independent variable in the form of brand charateristic (X1), company characteristic (X2), and brand-consumer characteristic (X3) have the influence which significant to dependent variable by that is brand loyalty so that the hypothesis at this research was accepted. While based on result the t test proven by that independent variable by partially have an effect on by significant to dependent variable so that first hypothesis at this research was accepted. Independent variable which is dominant influencing to the brand loyalty is brand-consumer characteristic variable so that second hypothesis was accepted.